Profiles of COVID-19 clinical trials in the Chinese Clinical Trial Registry - Peng Xu; Xiangyu Xing; Keying Yu; Zhiguo Lv; Huijing Cui; Yuhang Shi; Tianying Chang; Dongmei Zhang; Yibin Zhang; Kai Wang; Jing Lu; Qingxia Huang; et al. (Emerging Microbes and Infections, 2020)
ABSTRACTThe COVID-19 pandemic has caused a global public health crisis. There is a pressing need for evidence-based interventions to address the devastating clinical and public health effects of the COVID-19 pandemic. The Chinese scientists supported by private and government resources have adopted extensive efforts to identify effective drugs against the virus. To date, a large number of clinical trials addressing various aspects of COVID19 have been registered in the Chinese Clinical Trial Registry (ChiCTR), including more than 200 interventional studies. Under such an urgent circumstance, the scope and quality of these clinical studies vary significantly. Hence, this review aims to make a comprehensive analysis on the profiles of COVID-19 clinical trials registered in the ChiCTR, including a wide range of characteristics. Our findings will provide a useful summary on these clinical studies since most of these studies will encounter major challenges from the design to completion. It will be a long road for the outcomes of these studies to be published and international collaboration will help the ultimate goals of developing new vaccines and anti-viral drugs.